Myths and facts about functional neurological disorders: a cross-sectional study of knowledge and awareness among medical students and healthcare professionals in Iraq - Ahmed Hashim; Essam M Al-Sibahee; Sajjad Al-Badri; Nabeel Al-Fatlawi (BMJ Neurology Open)
Background Functional neurological disorder (FND) is a complex condition with neurological symptoms but no clear structural or biochemical explanation. Myths and misconceptions about FND can lead to misdiagnosis and inappropriate treatment. This study aimed to assess knowledge and common myths about FND among medical students and practitioners.Methods Data were collected from 324 participants using a structured questionnaire. The questionnaire included demographics, general information about FND and myths about FND. Data were analysed using non-parametric tests and Spearman’s r for correlations.Results The majority of participants were clinical-years medical students (65.1%) and female (59.6%). Overall, knowledge about FND was limited, with a mean score of 42.3% of correct answers. Common myths included the belief that FND is a psychological disorder and that patients feign symptoms. Knowledge scores differed significantly among different grades/experience levels, with postgraduate practitioners having the highest scores. There was a positive correlation between knowledge scores and confidence in managing FND.Conclusion This study highlights the prevalence of myths and misconceptions about FND among medical students and practitioners, emphasising the need for accurate education to improve diagnosis and management. Healthcare professionals should take a biopsychosocial approach to FND, considering the complex interplay between biological, psychological and social factors. Efforts to increase awareness and reduce stigma associated with FND are crucial for promoting better care. Targeted educational interventions may be beneficial to improve the understanding and management of FND among medical professionals.